Pengaruh Sikap, Norma Subjektif, Dan Persepsi Kontrol Perilaku Terhadap Minat Beli Skincare Ms.Glow Beauty ( Studi Kasus Pada Masyarakat Cikarang Usia 20-30 Tahun ) - Rohmah, Nur; Maulina, Anita; Arizona, Annisa (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The objective of this study is to analyze how much interest of Cikarang community to skincare Ms.Glow beauty with approach of Theory Of Planned Behavior The data was collected from questionnaire with 135 respondents. This study used a descriptive analysis methodology with quantitative approach which is analyzed with use of multiple linear analysis using SPSS version 29. Result of this study identified that Attitude has positively affected to Buying Interest of skincare Ms.Glow beauty in the Cikarang Community with value of 0.243 and Conduct Control Perception also has positively affected to Buying Interest of skincare Ms.Glow beauty in the Cikarang Community with value of 0.274. However, Subjective Norm has not affected to Buying Interest of Ms.Glow beauty in Cikarang community with value of 0.006.